2017
DOI: 10.1080/03075079.2017.1351428
|View full text |Cite
|
Sign up to set email alerts
|

The re-production process of gender bias: a case of ICT professors through recruitment in a gender-neutral country

Abstract: Women's underrepresentation in the fields of science and technology is strong; both in software houses and academic posts. We focus on the academic field by gender sensitive analysis of computer science academics. The general picture given by statistics' meta-analyses illustrates male dominance even in Finland, which is often presented as a country which values gender equality high. For achieving deeper understanding about the process of gender bias reproduction, we focus on one university and its selection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Just as color-blind ideology associates color with negative characteristics and invalidates one’s racial identity, a gender-neutral mind-set that dismisses the role of gender (Tiainen & Berki, 2017) especially within the STEM field does the same. Men and women of color will experience the White-male dominated STEM environment differently.…”
Section: Two Models That Inform Bssimentioning
confidence: 99%
“…Just as color-blind ideology associates color with negative characteristics and invalidates one’s racial identity, a gender-neutral mind-set that dismisses the role of gender (Tiainen & Berki, 2017) especially within the STEM field does the same. Men and women of color will experience the White-male dominated STEM environment differently.…”
Section: Two Models That Inform Bssimentioning
confidence: 99%
“…Five of these comments refer to gender-based discrimination as such (#1, #3, #5, #6, #8). Here, two aspects already reported in previous literature, namely negative prejudice on women and better working conditions for men [12,27,28,30,31] are addressed, but only by one response each. In addition, four comments address a lack of compatibility between career perspectives and family life, and are hence indirectly related to gender imbalances (#1, #2, #4, #7).…”
Section: Discussionmentioning
confidence: 99%
“…The Swiss Equal Opportunity Program included (i) an incentive (sub-)program a reduced integration of women in professional academic networks, the lower career ambitions of women compared to men, and less self-confidence in their own academic capabilities [9,25,26]. Other contributing factors are negative biases in the perception of female applications [27][28][29], better working conditions for men as compared to females at universities [12,30,31], and a high workload of females with academic service activities negatively impacting research productivity [32].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars found that gender discrimination begins in the recruitment phase, continues over time with career promotions and influences the way in which the scientific evaluation processes are constructed (Bystydzienski et al, 2017;Falcinelli and Guglielmi, 2014;Tiainen and Berki, 2019;Weisshaar, 2017). Bias against female candidates is one of the reasons why women are prevented from entering and reaching the upper levels of an academic careers (Van den Brink and Benschop, 2012;Verge et al, 2018).…”
Section: Academic "Glass-ceiling"mentioning
confidence: 99%